Effects of Fortified Laying Hen Diet with Moringa oleifera Leaves and Goji Berries on Cholesterol and Carotenoid Egg Content - Maria Maisto; Fortuna Iannuzzo; Elisabetta Schiano; Roberto Ciampaglia; Angiola Labanca; Domenico Montesano; Vincenzo Piccolo; Pasquale Rossi; Gian Carlo Tenore (Foods, 2022)
The biofortification of basal laying hen feed with natural matrices can improve the beneficial potential of eggs produced without relying on artificial fortification. The present study aimed to evaluate the effects of hen diet supplementation with dried Moringa leaves (DML) and goji berries (DGB) on egg functional properties in terms of cholesterol and carotenoid content. Forty Lohman Brown Classic laying hens were randomly divided into four groups. The control group (G1) received the basal poultry diet, group G2 received a diet with 5% DML + 10% DGB, group G3 received a diet with 3% DML + 7% DGB, and group G4 received a diet with 15% DML. HPLC-DAD analysis showed that feed supplementation positively influenced the egg carotenoid content, with a valuable increase in xanthophylls concentration, especially lutein (+333.24% in G4, +258.15% in G2, +189.24% in G3, compared to G1). The same trend was also followed by the β-carotene concentration (+181.38% in G3 and +116.01% in G4, compared to G1). Furthermore, the eggs obtained from G3 showed the lowest cholesterol content (−47.08%). Additionally, the performed antioxidant assays showed maximum activity in G2 (+39.11 compared to G1 for the DPPH test) and in G4 (+31.11 compared to G1 for the ABTS test). In conclusion, the G2 experimental diet could be potentially used in poultry industries to produce “functional eggs”.